HUBUNGAN ANTARA PEMAHAMAN KEBHINEKAANDENGAN SIKAP TOLERANSI PADA PESERTA DIDIK KELAS XSMA NEGERI COLOMADU TAHUN PELAJARAN 2024/2025 - Nita Rahma Rosa; Anita Trisiana; Ama Farida Sari (Jurnal Global Citizen : Jurnal Ilmiah Kajian Pendidikan Kewarganegaraan, 2026)
The purpose of this study was to determine a correlation between understanding diversity and attitudes of tolerance at the tenth-grade students of SMA N Colomadu in the 2024/2025 academic year. This research was conducted at SMA N Colomadu. The population in this study was 322 students. The sampling technique was through proportional random sampling. The sample was 40 students. Data collection techniques were through questionnaires and observations. The data analysis technique used was the product moment correlation test using SPSS Statistic 27. The result of the study showed that the r-count value was greater than the r-table 0,913 > 0,312 at a significance level of 5% So, the hypothesis that stated there is a positive and significant correlation between understanding diversity and the attitude of tolerance of student in class X SMA N Colomadu in the 2024/2025 academic year. Keywords: Relationship, Understanding Diversity, Attitude of Tolerance.